Thought Suppression and Cognitive Ability: Investigating the role of cognitive load, inhibitory control and working memory capacity in the frequency of intrusive thoughts. - Einar Kári Bogason 1985- (2013)
This study sought to investigate the role of cognitive load, working memory capacity (WMC) and proactive inhibition (PI) in suppression of a personally relevant intrusive thought. It also investigated the relationship between thought intrusions and mood, OCD-related appraisals and symptoms. In total, 105 female students at the University of Iceland took part in an experiment where their working memory capacity and proactive inhibition were measured before they took part in a thought suppression task involving a personal intrusive thought. Participants were randomly assigned instructions in the first interval to either suppress the thought during cognitive load, to suppress it without load or not to suppress it at all. In the second interval all participants received the same instructions to monitor their thoughts. The study found support for an immediate enhancement effect of thought suppression with cognitive load. Contrary to the hypotheses this relationship was not mitigated by WMC or PI. No effects of thought rebound were found. Measures of anxiety and appraisals of thought suppression failure had significant correlations with thought intrusion frequencies in both intervals of the thought suppression task. Measures of OCD related appraisals and symptoms were associated with greater thought intrusion frequencies only in the second interval of the task.